2019
DOI: 10.1371/journal.pone.0221754
|View full text |Cite
|
Sign up to set email alerts
|

When does activism benefit well-being? Evidence from a longitudinal study of Clinton voters in the 2016 U.S. presidential election

Abstract: Contrary to the expectations of many, Hillary Clinton lost the 2016 U.S. presidential election. The initial shock to her supporters turned into despair for most, but not everyone was affected equally. We draw from the literature on political activism, identity, and self-other overlap in predicting that not all Clinton voters would be equivalently crushed by her loss. Specifically, we hypothesize that pre-election measures of political activism, and level of self-other identification between participants and Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
3
10
1
Order By: Relevance
“…Some research suggests that participation in collective action groups can have benefits for well-being (e.g., Cherniss, 1972;Klar & Kasser, 2009). However, as Vestergren et al (2016) note, the underlying psychological processes remain underexamined in most of these studies: suggestions have included emotional expression (Foster, 2014), working toward something bigger than the self (Dwyer et al, 2019), and social support (Vestergren et al, 2019). A further suggestion is that action which brings about social change in line with the definition of an otherwise subordinated identity can produce well-being, in the form of empowerment (Drury et al, 2015).…”
Section: A Social Cure For the Stresses Of Giving Support In An Emerg...mentioning
confidence: 99%
“…Some research suggests that participation in collective action groups can have benefits for well-being (e.g., Cherniss, 1972;Klar & Kasser, 2009). However, as Vestergren et al (2016) note, the underlying psychological processes remain underexamined in most of these studies: suggestions have included emotional expression (Foster, 2014), working toward something bigger than the self (Dwyer et al, 2019), and social support (Vestergren et al, 2019). A further suggestion is that action which brings about social change in line with the definition of an otherwise subordinated identity can produce well-being, in the form of empowerment (Drury et al, 2015).…”
Section: A Social Cure For the Stresses Of Giving Support In An Emerg...mentioning
confidence: 99%
“…Previous research has found a positive relationship between collective action participation and well‐being (Dwyer et al, 2019; Vestergren et al, 2017). However, our results show that lower political trust in the system is associated with lower levels of self‐reported well‐being through their more engagement in offline (Study 1) and online (Study 2) collective action.…”
Section: Discussionmentioning
confidence: 92%
“…Through this paper, we aim to examine the referendum and the 2018 election in Turkey, as well as the viral campaigns and protests that bridged them, in line with the theoretical factors that influence individual outcomes as they relate to political trust, political engagement and well-being. While participation in collective action has previously been associated with well-being (Dwyer et al, 2019;Vestergren et al, 2017), to our knowledge, no previous study has investigated how collective action may mediate the relationship between political trust and well-being in authoritarian contexts. In addition, political trust has mostly been measured in democratic contexts (Helliwell et al, 2020), with some research in emerging democracies (see Carlin, 2011;Catterberg & Moreno, 2006) but little to no research that we know of in authoritarian contexts (but see Cinar &Kose, 2020 andSika, 2020 for some exceptions).…”
Section: Introductionmentioning
confidence: 97%
“…This may be because the BLM movement elicited a desire to join the movement to show solidarity in protesting systemic discrimination, racism, and police brutality against Black and Racialized communities. Indeed, evidence suggests that political activism may be an effective coping strategy to mitigate psychological distress and isolation during intense periods of transition (Hope et al, 2018 ) and that political activism and striving for the welfare of others is associated with more psychological well-being (Dwyer et al, 2019 ). Thus, our results are in line with prior research and may suggest that participating in the movement led to greater feelings of unity.…”
Section: Discussionmentioning
confidence: 99%
“…The BLM global network, which is committed to dismantling the systems of oppression that have sustained the trauma and pain of Black and other Racialized communities for generations (Bartholomew et al, 2018 ), became the face of the movement (Black Lives Matter, 2013 ; Burch et al, 2021 ). Previous research shows that engaging in political activism may act as a protective factor for certain young adults (Ballard et al, 2020 ) and is associated with higher levels of psychological well-being (Dwyer et al, 2019 ). Additionally, political activism may mitigate stress and isolation during intense periods of transition (Hope et al, 2018 ).…”
mentioning
confidence: 99%